Trauma and autobiographical memory: contents and determinants of earliest memories among war-affected Palestinian children. Issue 10 (26th November 2017) - Peltonen, Kirsi; Kangaslampi, Samuli; Qouta, Samir; Punamäki, Raija-Leena
ABSTRACT: The contents of earliest memories (EM), as part of autobiographical memory, continue to fascinate scientists and therapists. However, research is scarce on the determinants of EM, especially among children. This study aims, first, to identify contents of EM of children living in war conditions, and, second, to analyse child gender, traumatic events and mental health as determinants of the contents of EM. The participants were 240 Palestinian schoolchildren from the Gaza Strip (10–12 years, M  = 11.35, SD  = 0.57; 49.4% girls). They responded to an open-ended EM question, and reported their trauma exposures (war trauma, losses and current traumatic events), posttraumatic stress, depressive symptoms and psychosocial well-being, indicating mental health. The EM coding involved nature, social orientation, emotional tone and specificity. Results showed, first, that 43% reported playing or visiting a nice place as EM, and about a third (30%) traumatic events or accidents (30%) or miscellaneous events (27%). The individual and social orientation were almost equally common, the emotional tone mainly neutral (45.5%), and 60% remembered a specific event. Second, boys remembered more EM involving traumatic events or accidents, and girls more social events. Third, war trauma was associated with less positive emotional tone and with more specific memories.